Competitive Advantage Engineering, Procurement and Construction (EPC) dalam menentukan Corporate Strategy Industri Semen Study pada PT. X di Indonesia - Wahyono, Edy; Zuchrufudin, Irfan (Fakultas Ekonomi Universitas Wisnuwardhana, 2020)
Abstract: Competition in the cement industry in Indonesia is increasinglycompetitive with the entry of foreign cement companies, especially fromChina. To be able to compete with CEOs of companies in the cementindustry, innovations include evaluation of the EPC industry for CementManufacturing and sector holding strategies in expanding profits fromproduct differentiation. PT. Conducting competitive advantage evaluation tosupport target profit from business differentiation strategy using SWOTanalysis and pairwise comparison between evaluation factors to get priorityamong them using eigenvalue calculation to determine competitive strategy.Keywords: Innovation, Evaluation, Competitive advantage.